Evaluation of Glucose Results Measured by 2 Different Glucometer Brands - Tevfik Noyan; Murat Cihan; Esra Yiğit; Fatih Ahmet Uzdu (Journal of Turkish Clinical Biochemistry, 2026)
Objective: The aim of this study was to retrospectively evaluate the performance of 2 glucometer devices using the accuracy criteria specified in ISO 15197:2015. Methods: Glucose results obtained from Accu-Chek Inform II and Sejoy BG-707 glucometers, which measure according to the glucose dehydrogenase principle, were compared with glucose results obtained from the Cobas 8000 c702 autoanalyzer, which measures using the hexokinase method. Since the minimum number of patients required according to the ISO 15197:2015 protocol is 100, a total of two hundred patients were included using 2 independent samples, with 100 patient results included for each device. Results: When compared with the autoanalyzer, the Passing-Bablok regression equation for the Accu-Chek brand glucometer was y= 4.606 + .965x, and for the Sejoy brand glucometer y= 6.411 + .964x. In the Bland–Altman plot, the mean difference between glucose values compared to the hexokinase method was for the Accu-Check brand glucometer, 1.41 mg/dL (.08 mmol/L), and for the Sejoy brand glucometer, .09 mg/dL (.005 mmol/L). Furthermore, 98% of the Accu-Chek Inform II results and also 98% of the Sejoy BG-707 results met the ISO 15197:2015 accuracy criteria. In addition, all results for both glucometers were located within Zone A of the Consensus Error Grid. Conclusion: The results of the study showed that both glucometer measurement results were appropriate and reliable according to the ISO 15197:2015 guideline criteria, demonstrated strong agreement with autoanalyzer results using the hexokinase method, and revealed no statistically significant difference between glucometer and autoanalyzer measurements.